Perspektif Wahana Lingkungan Hidup (WALHI) Sumsel Pada Film Dokumenter Baradwipa Karya Watchdoc Documentary - Rio Roma Dhoni (Program Studi Jurnalistik, Universitas Islam Negeri Raden Fatah Palembang, 2023)
Film is one of the various types of mass media where audio and visual are put together and packaged in such a way as to produce a work, namely a spectacle that is interesting and easily leaves an impression on the minds of the audience. Apart from being a means of entertainment, film is also a means of providing information, a means of educating, and also persuading the audience. Like the documentary film genre that is produced in accordance with the real facts in the field. Therefore, this study aims to find out how influential documentaries are among the public, especially documentaries on environmental issues, therefore researchers conducted research at the South Sumatran Forum for the Environment (WALHI) to find out their perspectives on the documentary film Baradwipa by Watchdoc Documentary which raised the impact of coal mining and PLTU on the island of Sumatra. This research is a qualitative descriptive research with the object of research being members of the South Sumatran Forum for the Environment (WALHI), the number of members interviewed was 5 people based on the specified criteria. The methods used in data collection include various methods including in-depth interviews, observation, and documentation. The research data sources come from theoretical books, documents and information related to the Baradwipa documentary film. The results of this study indicate that the perspective of Walhi members of South Sumatra said that the Baradwipa film was very good because it was included in a campaign movement through social media. The campaign has the advantage of being able to reach a wide audience where the campaign is broadcast via social media. As we know now, almost all people are inseparable from social media. is a new breakthrough for Walhi South Sumatra in the future.